Chemsex Drug Use among a National Sample of Sexually Active Men who have Sex with Men, – American Men's Internet Survey, 2017–2020. (16th April 2023) - Ivey, Kaitlyn; Bernstein, Kyle T.; Kirkcaldy, Robert D.; Kissinger, Patricia; Edwards, O. Winslow; Sanchez, Travis; Abara, Winston E.
Abstract: Background: Chemsex is the intentional use of drugs to enhance sexual activity. Chemsex drug use among men who have sex with men (MSM) is associated with sexual behaviors that increase sexually transmitted infection (STI) risks and adverse mental health outcomes. However, published data are largely based on MSM recruited from STI clinics. There are limited data about use of chemsex drugs among national samples of MSM in the United States. Using data from the American Men's Internet Survey (AMIS), we assessed the prevalence and correlates of use of chemsex drugs among sexually active MSM in the United States. Methods: We used data from the 2017 to 2020 AMIS cycles to examine the prevalence of chemsex drug use in the past 12 months among MSM. We calculated prevalence ratios (PR) and 95% confidence intervals (CI) to compare chemsex drug use across demographic, behavioral, and mental health factors. Results: Of 30, 294 MSM, 3, 113 (10.3%) reported chemsex drug use in the past 12 months. Of the 3, 113 MSM who reported chemsex drug use, 65.1% reported ecstasy use, 42.5% reported crystal methamphetamine use, and 21.7% reported GHB use. Factors associated with chemsex drug use included condomless anal sex (PR = 1.93, 95%=1.69–2.20), problem drinking (PR = 2.36, 95% = 2.13–2.61), bacterial STI test (1.84, 95% CI = 1.68–2.02) and probable serious mental illness (PR = 1.92, 95% = 1.76–2.09). Conclusion: Chemsex drug use is associated with behaviors that increase STI risk and mental distress among MSM. Health programs that serve MSM can consider screening for chemsex drug use and offering sexual and mental health promotion and risk reduction interventions when necessary.